1994
DOI: 10.1128/jb.176.13.3992-4002.1994
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of benzothiophene by isopropylbenzene-degrading bacteria

Abstract: Isopropylbenzene-degrading bacteria, including Pseudomonas putida RE204, transform benzothiophene to a mixture of compounds. Induced strain RE204 and a number of its TnS mutant derivatives were used to accumulate these compounds and their precursors from benzothiophene. These metabolites were subsequently identified by 1H and 13C nuclear magnetic resonance spectroscopy and gas chromatography-mass spectrometry. When strain RE204 was incubated with benzothiophene, it produced a bright yellow compound, identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 32 publications
2
60
0
Order By: Relevance
“…However, no bacterial strain has been found to grow on benzothiophenes as the sole carbon source, and all reported biotransformations of benzothiophenes are based on cometabolism. Attacks on the thiophene ring of benzothiophenes lead to the formation of sulfoxides and sulfones, or to ring opening and the formation of 2-mercaptomandelaldehyde and 2-mercaptophenylglyoxalate [158][159][160]. Catabolism of dibenzothiophene is catalyzed by distinct enzymes in two pathways (Scheme 7).…”
Section: Alicyclic Hydrocarbonsmentioning
confidence: 99%
“…However, no bacterial strain has been found to grow on benzothiophenes as the sole carbon source, and all reported biotransformations of benzothiophenes are based on cometabolism. Attacks on the thiophene ring of benzothiophenes lead to the formation of sulfoxides and sulfones, or to ring opening and the formation of 2-mercaptomandelaldehyde and 2-mercaptophenylglyoxalate [158][159][160]. Catabolism of dibenzothiophene is catalyzed by distinct enzymes in two pathways (Scheme 7).…”
Section: Alicyclic Hydrocarbonsmentioning
confidence: 99%
“…Six metabolites of BT were detected by GC-MS: BTO 2 and 2-mercaptobenzoic acid were identified by comparison of their retention times and mass spectra with those of authentic compounds; 2-hydroxybenzothiophene, 3-hydroxybenzothiophene, benzothiophene-2,3-dione and BTO were identified by comparison of their mass spectra with published data (Saftić et al, 1992;Eaton & Nitterauer, 1994;Kropp et al, 1994b;Gilbert et al, 1998). These results indicate that strain XLDN2-5 is able to catalyse lateral dioxygenation and S oxidation on the thiophene ring of BT.…”
Section: Microbial Transformation Of Benzothiophenesmentioning
confidence: 99%
“…However, no bacterial strain has been found that is able to grow on benzothiophenes as the sole carbon source, and all reported biotransformations of benzothiophenes are based on cometabolism. Attacks on the thiophene ring of benzothiophenes lead to the formation of sulfoxides and sulfones, or to ring opening and the formation of 2-mercaptomandelaldehyde and 2-mercaptophenylglyoxalate (Saftić et al, 1992;Eaton & Nitterauer, 1994;Gilbert et al, 1998). Interestingly, it has been reported that BTO is trapped as a Diels-Alder-type disulfoxide cycloadduct, which yields (Kropp et al, 1994b).…”
Section: Introductionmentioning
confidence: 99%
“…The mass spectra were compared with the computer database of the National Institute of Science and Technology (NIST) mass spectral library and the published mass spectra of BT intermediates. 22,23 The mass spectra of peaks at retention times 6.57, 10.00, and 11.04 min have a near 100 : 4.4 ratio based on the isotope ion peaks at m/z values of M + and (M+2) + . This ratio indicates the presence of a sulfur atom (Figure 1b-e).…”
Section: Resultsmentioning
confidence: 99%
“…22 The m/z value of the molecular ion of the peak at 11.04 min (Figure 1e Figure 1d. 23 The mass spectra correspond potentially to the isomers 2-, 3-, 4-, 5-, 6-, or 7-hydroxybenzothiophene. Among them, the peaks at 10.07 and 10.25 min appear to be 2-hydroxy-benzothiophene and 3-hydroxybenzothiophene.…”
Section: Resultsmentioning
confidence: 99%